STUDI FOLKLORE EKSISTENSI SENI PERTUNJUKAN JARAN KEPANG “PATI KENANGA LIMA PANDAWA” MEDAN MARELAN - Andika, Riki; Purba, Mauly (SIWAYANG Journal: Publikasi Ilmiah Bidang Pariwisata, Kebudayaan, dan Antropologi, 2023)
This research aims to determine the factors that encourage the existence of the Pati Kenanga Pandawa Lima jaran kepang performance in Medan Marelan District. The benefit of this research is that it adds to the author's insight in compiling scientific work and it is hoped that this research will continue to maintain the existence of the preservation of Jaran Kepang which is increasingly disappearing as time goes by. The approach used by the author is a qualitative approach. This research uses data collection techniques by observation, in-depth interviews with several informants, namely cultural figures, arts and culture teachers, Jaran Kepang leaders, as well as informants who are involved in Jaran Kepang art performances such as Handlers, Musical Instrument Players, and Dancers. The results of this research show that the Jaran Kepang Pati Kenanga Pandawa Lima Marelan performance is still in demand and appreciated by the local community. Cultural figures consider that the Jaran Kepang Art Performance can be used as entertainment for the local community because it attracts public attention through supernatural attractions.